2016
DOI: 10.18632/oncotarget.7027
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gene sequencing for risk assessment in patients with early-onset or familial breast cancer

Abstract: Since BRCA mutations are only responsible for 10–20% of cases of breast cancer in patients with early-onset or a family history and since next-generation sequencing technology allows the simultaneous sequencing of a large number of target genes, testing for multiple cancer-predisposing genes is now being considered, but its significance in clinical practice remains unclear. We then developed a sequencing panel containing 68 genes that had cancer risk association for patients with early-onset or familial breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 39 publications
4
75
0
7
Order By: Relevance
“…Mutations in the ATM gene have been described in YWBC and are considerably more frequent when there is a familial history [102][103][104][105][106][107] .…”
Section: Atmmentioning
confidence: 99%
“…Mutations in the ATM gene have been described in YWBC and are considerably more frequent when there is a familial history [102][103][104][105][106][107] .…”
Section: Atmmentioning
confidence: 99%
“…13,14 Recent evidence suggests mutations in PALB2, ATM , and the genes responsible for the MRN complex, RAD50, MRE11 , and NBN , play a role in hereditary cancers. 15,16 For example, PALB2 mutation carriers have a lifetime risk of breast cancer development of approximately 50%, 17,18 and ATM mutation carriers are at higher risk for development of breast, 19,20 pancreatic, 21,22 and prostate cancers. 23,24 …”
Section: Introductionmentioning
confidence: 99%
“…Although studies have demonstrated the clinical benefit of multiple-gene sequencing for the assessment of patients with high-risk hereditary cancer [21,22], little information is currently available regarding the value of multiple-gene sequencing for the assessment of the risk of hereditary breast cancer in China. The goal of this study was to identify the variant spectrum for the clinical and genetic characterization of familial breast cancer in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%